Effect of fruit thinning on nut characteristics and leaf mineral nutrient concentration in walnut (Juglans regia) cv. Xiangling (Current Horticulture, 2024)
The experiment was conducted to find out the effect of fruit thinning in walnut (Juglans regia L.) ` final nut number, nut weight, kernel rate, nuts mineral nutrients concentration and mineral nutrients concentration within leaves during growing season of 2014 and 2015 at Baoking in Hubai, China. The fruit thinning affected nut uniformity more than final nut number, weight and kernel rate. Fruit thinning showed non-significant effect on macro nutrient (N, P and K) concentrations within kernel, but had significant effect on micronutrient (Fe, Zn and B) concentration. With more fruits been retained, N, K, Fe, B and Zn concentrations within leaves increased significantly during the fruit developing. Thus, fruit thinning management for early-bearing commercial orchard could obtain more commercially valuable nuts and reduce mineral nutrients consuming.
Keywords: Concentrations; Fruit thinning; Leaf mineral nutrient; Nut characteristics